Relative Clauses in Minangkabau, Indonesian, English Languages (Typology Study) - Akmal Akmal; Mulyadi Mulyadi (Randwick International of Education and Linguistics Science Journal, 2021)
Minangkabau and Indonesian languages are an Austronesian. In this study, it was focused on the typology study of three different languages, namely: Minangkabau, Indonesian, and English relative clauses. It aimed to find out the differences and the similarities of relative clauses among the three languages. This paper also outlines the Accessibility Hierarchy approach to the facts that describe building on relative clause construction. The data was taken from some conversations with Minangkabaunese friends and feedback from the writer as a native speaker of the language in the analysis as well as taking the findings of recent typological and theoretical studies of Austronesian languages into consideration. From the analysis, it is found that Minangkabau and Indonesian languages are same contsruction and the english is different between Minangkabau and Indonesian languages. In the English, it is also possible to have object focus which called object fronting.